2014
DOI: 10.1021/je500345n
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Dexamethasone in Supercritical Carbon Dioxide with and without a Cosolvent

Abstract: The solubility of dexamethasone, a synthetic glucocorticoid, in supercritical CO 2 and together with 3.0 mol % ethanol as a cosolvent was measured at different temperatures (313.2, 318.2, and 323.2) K and pressures ranging from (10.0 to 25.0) MPa by a static analytical method. The obtained solubility of dexamethasone was between 1.19·10 −6 and 1.52·10 −6 in pure supercritical CO 2 and between 1.97·10 −6 and 2.98·10 −6 in supercritical CO 2 with a cosolvent. The experimental data in supercritical CO 2 in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In the case of β-carotene, solubility and adsorption equilibria in propane were investigated, while Jin et al reported the solubility of 4-aminosalicylic acid in 1,1,1,2-tetrafluoroethane (R134a). , Generally, hydrophobic and polar substances are almost insoluble in SC CO 2 . To enhance the solubility of these substances, cosolvents like ethanol, ethyl acetate, and acetone can be used. …”
Section: System Investigatedmentioning
confidence: 99%
“…In the case of β-carotene, solubility and adsorption equilibria in propane were investigated, while Jin et al reported the solubility of 4-aminosalicylic acid in 1,1,1,2-tetrafluoroethane (R134a). , Generally, hydrophobic and polar substances are almost insoluble in SC CO 2 . To enhance the solubility of these substances, cosolvents like ethanol, ethyl acetate, and acetone can be used. …”
Section: System Investigatedmentioning
confidence: 99%
“…Therefore, the increase in extraction temperature enhances diffusivity and solute-solvent interactions and also reduces the viscosity and surface tension of the solvent which allows it to diffuse more easily in the plant matrix. Tang et al (2014) reported a similar finding whereby an increase in temperature from 313.2 to 323.2 K enhanced the dexamethasone solubility. This is because a robust polar interaction and hydrogen bonding between modifier (ethanol) and dexamethasone is detected as the temperature rose.…”
Section: Solubility Datamentioning
confidence: 56%
“…And the amount of dexamethasone in drug‐loading porous PLGA scaffolds kept going down due to the dissolution in water in the leaching out of NaCl. Generally, the loss of dexamethasone in the process of scCO 2 foaming could be negligible because the solubility of dexamethasone was only 1.19 × 10 −6 –1.52 × 10 −6 mol/mol in scCO 2 . Even though a large amount of dexamethasone was lost in preparation of drug‐loading PLGA microspheres in this work, co‐dissolving in dichloromethane is still a practical method to incorporate dexamethasone into PLGA phase homogeneously, and dexamethasone‐loading capacity of porous PLGA scaffolds could be regulated by changing initial dexamethasone or NaCl addition to satisfy the requirements of clinical practice.…”
Section: Resultsmentioning
confidence: 89%